The Efficacy of Collaborative Strategic Reading in Enhancing Narrative Text Comprehension among Tenth-Grade Learners - Nurdiana Nurdiana; Afrizal Afrizal; Malinda Puspita (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Despite various efforts to enhance reading comprehension, a preliminary study revealed that tenth-grade students at Pekanbaru's State Islamic Senior High School faced challenges comprehending narrative texts. This quasi-experimental study aimed to determine whether Collaborative Strategic Reading (CSR) instruction could improve students' narrative text comprehension. A total of 202 students were randomly assigned to two groups: a control group receiving traditional instruction and an experimental group receiving CSR instruction. Pre- and post-tests were administered to both groups to assess their comprehension abilities. Data analysis using SPSS version 20 revealed a significant difference between the two groups, indicating that CSR instruction effectively enhanced narrative text comprehension. The effect size, however, was relatively weak (η² = 0.111). These findings suggest that incorporating CSR into English language instruction can positively impact students' comprehension of narrative texts, even though the effect size is relatively small. Future research is needed to further investigate the effectiveness of CSR in enhancing reading comprehension across different genres and grade levels.